Daily time series of groundwater recharge derived from temporal variation of water level - Teramoto, Elias Hideo [UNESP]; Crioni, Pedro Luiz Becaro [UNESP]; Chang, Hung Kiang [UNESP] (Springer Nature, 2021)
The estimation of groundwater recharge volume is a crucial requirement for the management of subsurficial water resources. The implementation of monitoring of the water table in shallow aquifers allows the seasonal variation in the water table induced by natural and anthropogenic factors. The assessment of groundwater recharge through analysis of the water table is commonly estimated by the water table fluctuation (WTF) method, an approach subject to uncertainty. Aiming to improve estimation of groundwater recharge, we proposed and tested a simple approach combining a numerical flow model with statistical analysis of cross-correlation. Our strategy produces a time-series of recharge that is able to generate the observed water-table fluctuation and may be especially useful in analyses of the hydrological balance. The obtained results showed that our approach was suitable and was capable of producing a time-series of monthly recharge, with groundwater recharge comprising 17% of total precipitation. The cross-correlation indicates that the most significant correlation (0.63) between precipitation and groundwater recharge is observed at a time lag of 1.5 months, suggesting fast movement of precipitated water toward the unsaturated zone.
Keywords: Guarani aquifer system; Numerical flow simulation; Recharge; Water table fluctutation